Biosimilars Would Reduce Health Care Costs But Are Yet Poorly Known – Patient Survey Study Among Biological Medicine Users - Pölkki M; Prami T (Dove Medical Press, 2024)
Mari Pölkki, Tuire Prami Oriola, Expert Services, Espoo, FinlandCorrespondence: Tuire Prami, Oriola Finland Oy, Orionintie 5, 02200 Espoo, Finland, Tel +358505468459, Email tuire.prami@oriola.comBackground: From the beginning of the year 2024, gradually implemented amendment to the Medicines Act will enable interchange of biological medicines in pharmacies in Finland. The legislative change aims to reduce health care costs.Methods: Opinions of the biological medicine users regarding substitution in pharmacies and knowledge about biological medicines were determined by a patient survey in community pharmacies and via patient organizations in Finland.Results: In total, 199 users of biological medicines responded to the survey. The respondents did not always know which product they were using, an originator or a biosimilar. This was more prominent among patients with biosimilars determined according to brand names. The more recently the biological medicine had been prescribed, the more likely a biosimilar was in use. Only about 40% of the respondents would enable pharmacies to substitute their biological medicine to a lower cost product. The most common obstacle to the idea of interchange in pharmacies was that the respondents wanted to keep the product the doctor had prescribed for them. In general, biosimilar users were more accepting towards possible interchange than originator users.Conclusion: Although the most recent treatments appear to be initiated with biosimilars, interchange in pharmacies could enable an efficient way to lower health care costs. However, guidance and awareness regarding biosimilars and biological medicines in general would improve patients' willingness towards the change, but also help pharmacists and prescribing doctors in their meaningful role.Plain Language Summary: The use of biological medicines and the costs thereafter are rapidly growing.In Finland, switching between an originator and a biosimilar currently requires doctor's prescription, but interchange in pharmacies will be possible in the beginning of year 2024.Due to notable differences in prices between biological medicines, active switching to lower cost products in pharmacies would restrain health care costs remarkably.Oriola Expert Services ran a survey with an electronic questionnaire among patients using biological medicines.Survey data were collected in pharmacies and via patient organizations.Oriola research team found out that patients do not generally know the differences between biological medicines, and if they are using an originator or a biosimilar.Despite the upcoming pharmacy substitution, future cost savings rely on decisions made by doctors at the time of prescribing biological medication.To ensure patient compliance, sufficient patient information about biosimilars is required.Keywords: biological medicine, originator, biosimilar, reference product, interchange